Design, analysis and fabrication of solar power bank using recycle battery / Aqil Hafiz Tsen Loong Tyan and Suhadiyana Hanapi - Tsen Loong Tyan, Aqil Hafiz; Hanapi, Suhadiyana (School of Mechanical Engineering, 2022)
My project PDC 2022 is a Solar power bank. As you know, a solar power bank is a storage device that obtains energy from the sun and uses it to charge various electronic gadgets like phones, tablets, laptops, torches, bulbs, and many more. The major feature of this project that makes it unique is that as long as there is sunlight, even just a little bit, the solar panel will draw power. I achieved my objective and the prototype is well functioning. The solar panel that I use on the power bank really draws power from sunlight and converts it to electricity. To use the solar panel, we just need to dry it under the sunlight and see whether the charging detector is blinking or not. If the charging detector blinks it means the battery is charging. My prototype has a light to help people torch in the dark area. To switch on the light, hold the button for 3 seconds to turn on the light. First click is to make the light slow blinks, second click is to make the blinking faster, and the third click is to turn off the light. To conclude, my projects support greenhouse technology because it uses sunlight as an energy supply. Lastly, this project can open the minds of people to save the environment